Group II metabotropic glutamate receptor blockade promotes stress resilience in mice - Highland, Jaclyn N. (Neuropsychopharmacology, 2019)
Stress is a leading risk factor for the onset and recurrence of major depression. Enhancing stress resilience may be a therapeutic strategy to prevent the development of depression in at-risk populations or its recurrence in depressed patients. Group II metabotropic glutamate receptor (mGlu(2/3)) antagonists have been recognized for antidepressant-like actions in preclinical models, but have not been evaluated for prophylactic effects. We assessed the role of mGlu(2/3) in modulating stress resilience using subtype-specific knockout mice lacking mGlu(2) (Grm2(−/−)) or mGlu(3) (Grm3(−/−)), and pharmacological manipulations of mGlu(2/3) activity during or prior to the induction and reinstatement of stress-induced behavioral deficits. Grm2(−/−), but not Grm3(−/−), mice exhibited reduced forced-swimming test immobility time and were resilient to developing inescapable shock (IES)-induced escape deficits. Grm2(−/−) mice were also resilient to developing corticosterone (CORT)-induced escape deficits and chronic social defeat stress-induced anhedonia. Pharmacological blockade of mGlu(2/3) with the antagonist LY341495 during stress prevented the development of IES- and CORT-induced escape deficits, while activation with the agonist LY379268 increased susceptibility to escape deficits. Prophylactic treatment with the LY341495, both systemically and via microinjection into the medial prefrontal cortex (mPFC), up to 7 days before IES, prevented both the induction of escape deficits and their reinstatement by brief re-exposure to IES up to 20 days after treatment. Overall, blockade of mGlu(2/3) enhanced stress resilience and deletion of mGlu(2), but not mGlu(3), conferred a stress-resilient phenotype, indicating that prophylactic treatments reducing mGlu(2) activity may protect against stress-induced changes underlying the development or recurrence of stress-induced disorders, including depression.